Pengaruh Profitabilitas, Harga Saham, Likuiditas Dan Ukuran Perusahaan Terhadap Nilai Perusahaan Sektor Pertambangan Yang Terdaftar Di Bursa Efek Indonesia (Periode 2018-2020) - I Wayan Warmita; Ni Wayan Alit Erlina Wati (UNHI Press, 2022)
This study aims to determine the effect of profitability, stock price, liquidity, company size on the value of mining sector companies listed on the IDX for the 2018-2020 period. The population in this study amounted to 46 companies and a sample of 44 companies was taken using purposive sampling method. The data used in this study is secondary data in the form of an annual report from 2018-2020 which is accessed through the website www.idx.co.id. The analytical method used is multiple regression analysis. The results showed that the profitability ratio proxied by Return On Assets (ROA) had a positive and insignificant effect on firm value, stock prices (Closing price) had a positive and significant effect on firm value, while liquidity was proxied by the Current Ratio (CR) and firm size as a proxy for the natural logarithm of total assets has a negative and significant effect on firm value